The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1007/s13197-014-1305-y
|View full text |Cite
|
Sign up to set email alerts
|

Grape seed extract and Zinc containing nutritional food supplement delays onset and progression of Streptozocin-induced diabetic cataract in Wistar rats

Abstract: Prevention of hyperglycemia and enhancement of antioxidant defense mechanisms remain major goals in the treatment of diabetic cataract. Earlier, we reported strong antihyperglycemic and in vitro antioxidant potential of the combined formulation of grape seed extract and Zincovit tablets. Therefore, the current study was designed to investigate effects of combined formulation of grape seed extract and Zincovit tablets against streptozocin-induced diabetic cataract in Wistar rats. Adult Wistar rats were selected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…When this defense mechanism is not complete or when ROS are excessively generated, additional protecting mechanisms of dietary anti-oxidants could be of a great significance. This explains the increased number of the proposed natural and synthetic anti-oxidative agents that treat reproductive hormonal imbalance and infertility induced by oxidative stress (35). Furthermore, recent results suggested that natural products containing anti-oxidants have the ability to protect testis against oxidative damages, lipid peroxidation, and impairment in anti-oxidant status induced by CCl 4 (3,13,35).…”
Section: Introductionmentioning
confidence: 99%
“…When this defense mechanism is not complete or when ROS are excessively generated, additional protecting mechanisms of dietary anti-oxidants could be of a great significance. This explains the increased number of the proposed natural and synthetic anti-oxidative agents that treat reproductive hormonal imbalance and infertility induced by oxidative stress (35). Furthermore, recent results suggested that natural products containing anti-oxidants have the ability to protect testis against oxidative damages, lipid peroxidation, and impairment in anti-oxidant status induced by CCl 4 (3,13,35).…”
Section: Introductionmentioning
confidence: 99%
“…One of the studies suggests that flavonoids possess antioxidant properties and have been shown to be potent inhibitors of LDL oxidation in vitro [9]. We had reported combined formulation of grape seed extract and Zincovit tablets for its strong in vitro, in vivo antioxidant, anti-hyperglycemic and anti-cataractogenic potential [10][11][12][13][14]. Consequently, the aim of the present study was to investigate the influence of single combined formulation of grape seed extract and Zincovit tablets (Nutritional food supplement) on lipid profile in normal and diet-induced hypercholesterolemic rats.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, we had reported combined formulation of grape seed extract and Zincovit tablets for its strong in vitro, in vivo antioxidant, anti-hyperglycemic and anti-cataractogenic potential [10][11][12][13][14]. A recent study has shown that a combination of IH636 grape seed proanthocyanidin extract and niacin-bound chromium can decrease total cholesterol, LDL and oxidized LDL level in hypercholesterolemic human subjects [9].…”
Section: Discussionmentioning
confidence: 99%
“…The rats were divided into six groups containing six rats in each group. Treatment was done for 7 days as follow: 6 Group I: Normal control rats were given 2% gum acacia (1 ml/kg/day; p.o). Group II: CCl 4 intoxicated control rats + 2% gum acacia (1 ml/kg/day; p.o) and simultaneously administered At the end of 7 th day treatment, all the experimental rats were kept overnight fasting and sacrificed by administering an overdose of ketamine, i.p.…”
Section: Experimental Designmentioning
confidence: 99%
“…Earlier, we had reported the antioxidant potential of combined formulation of grape seed extract and ZVT tablets. 5,6 Consequently, the aim of the present study was to investigate the antioxidant potential of ZVT syrup against CCl 4 intoxicated Wistar rats.…”
Section: Introductionmentioning
confidence: 99%